1993
DOI: 10.1111/j.1502-3885.1993.tb00190.x
|View full text |Cite
|
Sign up to set email alerts
|

Middle Weichselian to Holocene palaeoecology in the eastern Kattegat, Scandinavia: foraminifera, ostracods and 14C measurements

Abstract: Examination of a 10 m piston core from the eastern Kattegat revealed marine sediments spanning a period from the late Middle Weichselian to the Early Holocene. The oldest marine unit in the core is 14C‐dated to about 30,000–36,000 years BP. These sediments represent the Middle Weichselian Sandnes/Denekamp‐Hengelo Interstadial (upper part of stable isotope stage 3) and can be correlated to marine deposits from several localities in the Kattegat region by means of foraminifera. The Late Weichselian deposits comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 21 publications
0
16
0
1
Order By: Relevance
“…BOREAS This paper and a paper by Seidenkrantz & Knudsen (1993) are the first to report on cored marine Middle Weichselian sediments in the present offshore Kattegat (Fig. 1).…”
mentioning
confidence: 72%
“…BOREAS This paper and a paper by Seidenkrantz & Knudsen (1993) are the first to report on cored marine Middle Weichselian sediments in the present offshore Kattegat (Fig. 1).…”
mentioning
confidence: 72%
“…In a study from a site located to the north of Site M0060, ostracods were identified from the Upper Weichselian and Boreal sediments (Seidenkrantz & Knudsen 1993). The Upper Weichselian interval contained abundant Cytheropteron pseudomontrosiense.…”
Section: Discussionmentioning
confidence: 99%
“…). Seidenkrantz & Knudsen () studied a middle Weichselian to Early Holocene site in the eastern Kattegat. The authors indicate Cytheropteron pseudomontrosiense as a major ostracod species in the Upper Weichselian interval.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Marine intervals from the Middle Weichselian are, however, registered in many borings in the entire Kattegat region, e.g. on Lzs0 (Knudsen 1986), on Anholt (Seidenkrantz 1993a), the eastern Kattegat (Bergsten & Nordberg 1993;Seidenkrantz & Knudsen 1993), the southernmost Kattegat (Nielsen & Konradi 1990) and also in onshore cores and outcrops in northern Zealand (Petersen & Buch 1974;Konradi 1992).…”
Section: Saalian Eemian and Early To Middle Weichselianmentioning
confidence: 99%